Aerobic glycolysis fuels platelet activation: small-molecule modulators of platelet metabolism as anti-thrombotic agents - Kulkarni, Paresh P. (Haematologica, 2019)
Platelets are critical to arterial thrombosis, which underlies myocardial infarction and stroke. Activated platelets, regardless of the nature of their stimulus, initiate energy-intensive processes that sustain thrombus, while adapting to potential adversities of hypoxia and nutrient deprivation within the densely packed thrombotic milieu. We report here that stimulated platelets switch their energy metabolism to aerobic glycolysis by modulating enzymes at key checkpoints in glucose metabolism. We found that aerobic glycolysis, in turn, accelerates flux through the pentose phosphate pathway and supports platelet activation. Hence, reversing metabolic adaptations of platelets could be an effective alternative to conventional anti-platelet approaches, which are crippled by remarkable redundancy in platelet agonists and ensuing signaling pathways. In support of this hypothesis, small-molecule modulators of pyruvate dehydrogenase, pyruvate kinase M2 and glucose-6-phosphate dehydrogenase, all of which impede aerobic glycolysis and/or the pentose phosphate pathway, restrained the agonist-induced platelet responses ex vivo. These drugs, which include the anti-neoplastic candidate, dichloroacetate, and the Food and Drug Administration-approved dehydroepiandrosterone, profoundly impaired thrombosis in mice, thereby exhibiting potential as anti-thrombotic agents.